APLIKASI KELUHAN INFRASTRUKTUR DI LINGKUNGAN PUSAT PENGEMBANGAN DAN PEMBERDAYAAN PENDIDIK DAN TENAGA KEPENDIDIKAN (P4TK) PERTANIAN CIANJUR - Wahyudi Wahyudi; Indra Maulana Yusup Kusuma (LPPM STMIK BANDUNG, 2018)
Accountable excellent service is a vision of the institution that must be achieved and one of them is the availabil-ity of adequate infrastructure and in appropriate conditions even comfortable to be used by employees, to sup-port the performance of MR technicians in handling employee complaint reports that are not coordinated so an application system is needed to facilitate and streamline performance that is user friendly for employees as enti-ties that report complaints. The research uses data collection methods of observation and unstructured interviews to study system require-ments from the agency also with a structured approach to waterfall design model where the process includes defining requirements, system design and software, testing and implementation, system integration and opera-tions and maintenance. The first version of the Complaint infrastructure application was built web-based and mobile java programming for the Android version as a user application for employees because it was more fa-miliar with a user friendly and easy to use display. with the development of information technology now, and for the future there will be application development for agency needs, especially in education infrastructure ser-vices, by integrating this infrastructure complaint application with the system used by agencies for ease of eval-uation and reporting.